Dialysis Is Not Associated with Increased Risk of Perioperative Complications in TKA Patients after Adjusting for Pertinent Confounders - Gwam, Chukwuweike U.; Sultan, Assem; Rosas, Samuel; Sullivan, Rashad; Seem, Michael; Ohanale, Chiemena; Plate, Johannes F. (The Journal of Knee Surgery, 2020)
With a growing prevalence for chronic renal failure, arthroplasty surgeons will find it more likely to have dialysis dependent patients present for knee replacement. Previous retrospective studies using a matched cohort of patients have reported worse perioperative outcomes for dialysis-dependent patients. However, many of these studies failed to control for pertinent confounders. This study aims to fill in that void. The present study compares lengths of stay, discharge status, and 30-day outcomes between dialysis-dependent TKA recipients and a matched cohort of nondialysis dependent TKA recipients. The National Surgical Quality Improvement Program database was used to identify the study cohorts. Patients were propensity score matched based on patient-specific demographic variables, preoperative functional status, and preoperative laboratory values. Generalized regression models were conducted to assess the effects of dialysis dependency on perioperative outcomes. Dialysis dependent patients demonstrated longer mean lengths of stay (+1.14) and a lower likelihood for home discharge (odds ratio [OR] = 0.503). There was no increased risk of 30-day complications in dialysis dependent TKA patients. Our findings demonstrate no increased risk of 30-day complications after TKA when adjusting for pertinent confounders. This suggests TKA is safe for well optimized dialysis dependent patients prior to surgery.
Keywords: total knee arthroplasty; dialysis; perioperative outcomes; NSQIP; chronic kidney disease